Far-field angular distribution of the mean scattered intensity from strong diffusers by means of a near-field intensity pattern - Alvarez, Natalia (2010)
The speckle grain close to a diffuser medium carries information about the angles at which light is scattered. We propose the extension of a technique that allows obtaining the angular distribution of the scattered intensity in the far-field speckle pattern from the near-field speckle pattern produced by strong diffusers (whose roughness is greater than the illuminating wavelength). To illustrate this technique we applied it to the light scattered from ground glass diffusers. The experimental results are compared with those obtained by direct measurement of the angular distribution of the mean scattered intensity in the far field showing good agreement with each other. The advantages over the classical far-field methods are outlined.